2022
DOI: 10.3390/s22062380
|View full text |Cite
|
Sign up to set email alerts
|

Threats Detection during Human-Computer Interaction in Driver Monitoring Systems

Abstract: This paper presents an approach and a case study for threat detection during human–computer interaction, using the example of driver–vehicle interaction. We analyzed a driver monitoring system and identified two types of users: the driver and the operator. The proposed approach detects possible threats for the driver. We present a method for threat detection during human–system interactions that generalizes potential threats, as well as approaches for their detection. The originality of the method is that we f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…A wideband antenna array has been used in their experiment for both vehicle safety and comfort in conventional and future intelligent vehicles. Kashevnik et al have introduced threat detection during human-computer interactions in the in-cabin driver monitoring system [41].…”
Section: Related Workmentioning
confidence: 99%
“…A wideband antenna array has been used in their experiment for both vehicle safety and comfort in conventional and future intelligent vehicles. Kashevnik et al have introduced threat detection during human-computer interactions in the in-cabin driver monitoring system [41].…”
Section: Related Workmentioning
confidence: 99%
“…A threat detection method covering identified threats was proposed, and an operator-computer interaction interface reference model was presented showing how the driver monitoring process is organized and what information can be processed automatically and what information related to the driver's behavior has to be processed manually. The experimental results of the study indicated that when the driver monitoring system detects a threat in the compartment and notifies the driver, the number of threats significantly decreased [3]. Many global automotive corporations, including Toyota, Volkswagen, and Nissan, are presently engaged in research focused on driver attention systems.…”
Section: Introductionmentioning
confidence: 99%